Ellagic acid, phenolic acids, and flavonoids in Malaysian honey extracts demonstrate in vitro anti-inflammatory activity - Kassim, M.; Achoui, M.; Mustafa, Mohd Rais; Mohd, A.M.; Yusoff, K.M. (Elsevier, 2010)
Natural honey has been used in traditional medicine of different cultures throughout the world.This study looked into the extraction of Malaysian honey and the evaluation of the antiinflammatory activity of these extracts. It was hypothesized that honey extracts contain varying amounts of phenolic compounds and that they possess different in vitro anti-inflammatory activities. Honey extracts were analyzed using liquid chromatography mass spectrometry to identify and compare phenolic compounds, whereas high-performance liquid chromatography was used for their quantification. Subsequently, honey methanol extract (HME) and honey ethyl acetate extract(HEAE) were tested in vitro for their effect on nitric oxide production in stimulated macrophages.The extracts were also tested for their effects on tumor necrosis factor–α (TNF) cytotoxicity in L929 cells. The major phenolics in the extracts were ellagic, gallic, and ferulic acids; myricetin; chlorogenic acid; and caffeic acid. Other compounds found in lower concentrations were hesperetin, p-coumaric acid, chrysin, quercetin, luteolin, and kaempferol. Ellagic acid was the most abundant of the phenolic compounds recorded, with mean concentrations of 3295.83 and 626.74 μg/100 g of honey in HME and HEAE, respectively. The median maximal effective concentrations for in vitro nitric oxide inhibition by HEAE and HME were calculated to be 37.5 and 271.7 μg/mL, respectively. The median maximal effective concentrations for protection from TNF cytotoxicity by HEAE and HME were 168.1 and 235.4 μg/mL, respectively. In conclusion, HEAE exhibited greater activity in vitro, whereas HME contained a higher concentration of phenolic compounds per 100 g of honey